Subacute sclerosing pan encephalitis: An update - Kumar Saurabh; Varun Kumar Singh; Abhishek Pathak; Rameshwar Nath Chaurasia (Journal of Clinical and Scientific Research, 2021)
Despite increasing immunisation rates, developing countries continue to report subacute sclerosing pan encephalitis (SSPE). The defective measles virus causng SSPE persists in brain cells because of hypermutated M protein and deranged host's immune responses. Patients usually present with cognitive decline and myoclonus. However, atypical presentations such as seizures and visual loss are also quite common, causing wrong or delayed diagnosis in a significant number of cases. Diagnosis is based on suggestive clinical features, electroencephalographic findings and elevated cerebrospinal fluid (CSF) antimeasles antibody titre. Newer methods of reporting antibody levels such as CSF/serum quotient (CSQrel) result in increased specificity, but individual values of serum and CSF antimeasles antibody titres should also be checked if CSQrel is negative or equivocal. In highly suspicious cases with negative CSF antimeasles antibody profile, repeat testing should be done. Combination therapy with interferon-alpha and isoprinosine is the most common starting regimen. Intraventricular administration of interferon-alpha is theoretically the most effective route but requires meticulous hygiene and complications are frequent. Hence, the proper route and frequency of interferon-alpha treatment should be chosen depending on efficacy, affordability, disease stage and parent's expectations. Though treatment has largely remained unsatisfactory, reported rates of improvement or stabilisation (34%–35%) are much better than that for spontaneous remission (5%–10%). Fusion inhibitors and adenovirus-delivered small interfering RNA are being studied as new therapies. However, increasing immunisation rates can be the only long-term answer to tackle the menace of measles and its complications.